Four-valued expansions of Dunn-Belnap's logic (I): Basic characterizations - Pynko, Alexej P. (Bulletin of the Section of Logic, 2020)
Basic results of the paper are that any four-valued expansion L4 of Dunn-Belnap's logic DB4 is de_ned by a unique (up to isomorphism) conjunctive matrix ℳ4 with exactly two distinguished values over an expansion